THE IMPACT OF AGRICULTURAL LAND OWNERSHIP ON THE SUBJECTIVE WELLBEING OF FARMERS IN INDONESIA - Kartika Eka Pratiwi; Jossy Prananta Moeis (Jurnal Ekonomi dan Pembangunan, 2022)
Welfare measures began to shift to the condition of Subjective Wellbeing (SWB). Meanwhile, the welfare of farmers must be prioritized, one of which is to fulfill their basic needs in the form of agricultural land. Ironically, land inequality in Indonesia is still quite high. This study aims to see the impact of agricultural land ownership on the SWB score of farmers in Indonesia. This study uses data from the 2007 and 2014 IFLS and fixed effect estimation method and PSM to address sellection bias. Agricultural land tenure was found to have a consistent and positive effect on SWB even after controlling for income.